Emf response on human body model caused by side flashes and earth potential rise - Zakaria N.A.; Ali N.H.N.; Nordin F.H.; Mustafa N.B.A.; Amirulddin U.A.U.; Kadir M.Z.A.A. (Science and Engineering Research Support Society, 2023)
Most lightning fatalities take place in outdoor areas and it is reported that earth potential rise (EPR) contributes to the highest lighting injuries while side flash is the second highest. Due to the number of injuries caused by side flash and EPR events, there is a need to conduct thorough investigation on the electrical response to human body parts. Hence in this paper, the level of injuries on each body parts is determined based on the values and distributions of current, magnetic field, magnetic flux and energy produced by both EPR and side flash. Single line is generated from head to leg to measure the lightning effects on head, chest, hand and legs, which allow comparison to be made. The results show that side flash affects more on the upper part of the body while EPR affects more on the lower part of the body. However, individuals that are struck by EPR have higher probability to die compared to side flash since EPR produces higher value of current which is 0.032860 Wb/m on both feet compared to side flash, 0.01589 Wb/m on left hand which is more than the human body could withstand. 2020 SERSC.